Modeling subauroral polarization streams during the 17 March 2013 storm. Issue 3 (12th March 2015) - Yu, Yiqun; Jordanova, Vania; Zou, Shasha; Heelis, Roderick; Ruohoniemi, Mike; Wygant, John
Abstract The subauroral polarization streams (SAPS) are one of the most important features in representing magnetosphere‐ionosphere coupling processes. In this study, we use a state‐of‐the‐art modeling framework that couples an inner magnetospheric ring current model RAM‐SCB with a global MHD model Block‐Adaptive Tree Solar‐wind Roe Upwind Scheme (BATS‐R‐US) and an ionospheric potential solver to study the SAPS that occurred during the 17 March 2013 storm event as well as to assess the modeling capability. Both ionospheric and magnetospheric signatures associated with SAPS are analyzed to understand the spatial and temporal evolution of the electrodynamics in the midlatitude regions. Results show that the model captures the SAPS at subauroral latitudes, where Region 2 field‐aligned currents (FACs) flow down to the ionosphere and the conductance is lower than in the higher‐latitude auroral zone. Comparisons to observations such as FACs observed by Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE), cross‐track ion drift from Defense Meteorological Satellite Program (DMSP), and in situ electric field observations from the Van Allen Probes indicate that the model generally reproduces the global dynamics of the Region 2 FACs, the position of SAPS along the DMSP, and the location of the SAPS electric field around L of 3.0 in the inner magnetosphere near the equator. The model also demonstrates double westward flow channels in the dusk sector (the higher‐latitude auroral convection and the subauroral SAPS) and captures the mechanism of the SAPS. However, the comparison with ion drifts along DMSP trajectories shows an underestimate of the magnitude of the SAPS and the sensitivity to the specific location and time. The comparison of the SAPS electric field with that measured from the Van Allen Probes shows that the simulated SAPS electric field penetrates deeper than in reality, implying that the shielding from the Region 2 FACs in the model is not well represented. Possible solutions in future studies to improve the modeling capability include implementing a self‐consistent ionospheric conductivity module from inner magnetosphere particle precipitation, coupling with the thermosphere‐ionosphere chemical processes, and connecting the ionosphere with the inner magnetosphere by the stronger Region 2 FACs calculated in the inner magnetosphere model.